Theorizing social media and activism: where is community development?. (6th January 2020) - McCabe, Angus; Harris, Kevin
Abstract: There is a growing public and academic debate on the societal impacts of the internet and, in particular, social media. For its proponents, social media is a force for change, which can challenge entrenched hierarchies, redistribute power, democratize information, support mass mobilization and contribute to the building of global movements. Increasingly such positivist arguments are being questioned. Critics argue that it has become a sinister force, facilitating the spread of 'fake news', providing an instrument for citizen surveillance and re-enforcing neoliberal hegemony. The community development literature has barely engaged in those debates around social media that appear urgent in other disciplines. Social media has been seen as a value-free tool for broadcasting and dissemination, and neither evaluated as a force for change nor examined as an instrument of neoliberal intents. Although there is a community development literature on neoliberalism and globalization, it often accepts these, rather than critiques them, as the contexts within which community development operates. Challenging established power imbalances and enhancing citizen participation in democratic processes are purposes central to community development values. Analysis of wider literature raises questions with regard to the values embedded in the technologies from which enhanced levels of participation and engagement are expected to flow. It also raises questions about who benefits most from the affordances of these technologies. This article, drawing on an extensive literature review, presents the case for community development values to be asserted in these debates.